A meta-analysis on dose-response relationship between night shift work and the risk of breast cancer - Wang, F; Yeung, K L; Chan, W C; Kwok, C C H; Leung, S L; Wu, C; Chan, E Y Y; Yu, I T S; Yang, X R; Tse, L A (Annals of oncology, 2013)
This study aimed to conduct a systematic review to sum up evidence of the associations between different aspects of night shift work and female breast cancer using a dose-response meta-analysis approach. We systematicly searched all cohort and case-control studies published in English on MEDLINE, Embase, PSYCInfo, APC Journal Club and Global Health, from January 1971 to May 2013. We extracted effect measures (relative risk, RR; odd ratio, OR; or hazard ratio, HR) from individual studies to generate pooled results using meta-analysis approaches. A log-linear dose-response regression model was used to evaluate the relationship between various indicators of exposure to night shift work and breast cancer risk. Downs and Black scale was applied to assess the methodological quality of included studies. Ten studies were included in the meta-analysis. A pooled adjusted relative risk for the association between 'ever exposed to night shift work' and breast cancer was 1.19 [95% confidence interval (CI) 1.05-1.35]. Further meta-analyses on dose-response relationship showed that every 5-year increase of exposure to night shift work would correspondingly enhance the risk of breast cancer of the female by 3% (pooled RR = 1.03, 95% CI 1.01-1.05; Pheterogeneity < 0.001). Our meta-analysis also suggested that an increase in 500-night shifts would result in a 13% (RR = 1.13, 95% CI 1.07-1.21; Pheterogeneity = 0.06) increase in breast cancer risk. This systematic review updated the evidence that a positive dose-response relationship is likely to present for breast cancer with increasing years of employment and cumulative shifts involved in the work.